Trends and patterns of hormonal contraceptive prescribing for adolescents in primary care in the UK. Issue 3 (14th November 2014) - Rashed, Asia N; Hsia, Yingfen; Wilton, Lynda; Ziller, May; Kostev, Karel; Tomlin, Stephen
Abstract : Background: Hormonal contraceptives are the most common method used worldwide by teenagers to prevent unwanted pregnancies. To date there are limited data about such use by teenagers in the UK. This study investigated trends and patterns of hormonal contraceptive prescribing to adolescents aged 12–18 years in UK primary care between 2002 and 2011. Methods: A retrospective cohort study using the IMS Disease Analyzer database was conducted. All females aged 12–18 years with ≥1 prescription for a contraceptive drug between 1 January 2002 and 31 December 2011 were included. Annual prevalence of contraceptive drug prescribing was calculated, and indications for prescribing, and types of contraceptive drug prescribed, were examined. Results: In 2002, 13.7% (6135/44 532) of female adolescents received prescriptions for hormonal contraceptives, compared to 19.0% (6597/34 676) in 2011. The majority of female adolescents [2002: 76.2% (4676/6135); 2011: 65.7% (4334/6597)] received a contraceptive drug for 'contraceptive management'. The combined oral contraceptive (COC), 'progestogen+estrogen', was the most commonly prescribed. Although use of progestogen-only contraceptives was lower than COCs, the number of patients who received desogestrel pills and etonogestrel implants increased during the study period; levonorgestrel pill use declined. Only one injectable progestogen, long-acting depot medroxyprogesterone acetate, was prescribed. Conclusions: Use of hormonal contraceptives among adolescents increased between 2002 and 2011, and COC usage was dominant. The increasing use of hormonal contraceptives in adolescents, especially in younger adolescents, warrants further investigation, including research into the long-term safety of these medicines in this age group.